Understanding the Multiple Effects of PCBs on Lipid Metabolism - Shan Q (Diabetes, Metabolic Syndrome and Obesity : Targets and Therapy, 2020)
Qiuli Shan,1,2,* Hongmei Li,1,* Ningning Chen,1,* Fan Qu,1 Jing Guo1 1College of Biological Science and Technology, University of Jinan, Jinan 250022, People’s Republic of China; 2State Key Laboratory of Environmental Chemistry and Eco-Toxicology, Research Center for Eco-Environmental Sciences, Chinese Academy of Sciences, Beijing 100085, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiuli Shan Email bio_shanql@ujn.edu.cnAbstract: Polychlorinated biphenyls (PCBs) are a typical class of environmental contaminants recently shown to be metabolism-disrupting chemicals. Lipids are a highly complex group of biomolecules that not only form the structural basis of biofilms but also act as signaling molecules and energy sources. Lipid metabolic disorders contribute to multiple diseases, including obesity, diabetes, fatty liver, and metabolic syndromes. Although previous literature has reported that PCBs can affect lipid metabolism, including lipid synthesis, uptake, and elimination, few systematic summaries of the detailed process of lipid metabolism caused by PCB exposure have been published. Lipid metabolic processes involve many molecules; however, the key factors that are sensitive to PCB exposure have not been fully clarified. Here, we summarize the recent developments in PCB research with a focus on biomarkers of lipid metabolic disorders related to environmental exposures.Keywords: PCBs, metabolism-disrupting chemicals, hepatocytes, lipid metabolism